RESPON KLON RAMI TERHADAP PENYEMPROTAN ZAT PENGATUR TUMBUII DAN PUPUK PELENGKAP CAIR - SASTROSUPADI, ADJI; ROMLI, MOCH; SANTOSO, BUDI (Jurnal Penelitian Tanaman Industri, 1999)
Response of ramie clone on growth regulator spray and liquidfertilizer supplementThe experiment of growth regulator and fertilizer supplement applicaÂ¬ tion was conducted at the green house of RITFC from November 1995 to June 1996 to accelerate the vegetative growth of ramie clone Pujon 10. The objective of the research was to find out suitable growth regulator to accelarate the vegetative growth of ramie clone Hie treatments were the application of /.PI and PPC as the supplement to NPK fetilizer application through the soil. I lie application was conducted one time and two times. The research used a completely randomized block design with three replications Hie results showed that 7-PT was the fastest in accelerating the vegetative growth of ramie The suitable dosage was 1.0 litrc/ha applied twice on 15 and 25 days after cuting, 0.5 htre/ha/application. The increase of chinagrass by adding the growth regulator was 57.8% compared to NPK fertilizer only.